Ghetto Machines: Hip-Hop and Intra‑Urban Borders in Istanbul - Yıldırım, Kevin (Lidé města, 2015)
In this paper, I look at how the Istanbul hip-hop group Tahribad-ı İsyan has symbolized the expropriation of Sulukule, a predominantly Romani neighborhood demolished by municipal powers under the guise of urban renewal. By examining how the local government enacted this project, and showing how similar neoliberal city management policies instigated widespread social unrest across Turkey in 2013, I set the stage for a music video analysis that makes two ultimate claims. First, I propose that hip-hop enables the group to overcome the debilitating effects of enforced gentrification by recasting Sulukule’s urban decay as a “ghettocentric” urban landscape. Second, and in dialogue with the work of the Turkish urban geographers Ozan Karaman and Tolga Islam, I suggest that Tahribad-ı İsyan provides evidence of how music can construct bounded intra-urban identities amid discourses of borderless and open cities.